Reasons Deemed for an Unwanted Pregnancy: A Qualitative Study - mitra kheiriat; fereshteh zamanialavijeh; marzieh araban; fatemeh kheiriat (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Pregnancy could be one of the best personal and family event of a woman, but unwanted pregnancy is a health concern affecting maternal, infant and society health. The aim of this study was to deeply explore the mental aspects of unwanted pregnancy. Methods: A qualitative research in 2013 was done in Behbahan and Ahvaz. Data collection was performed through unstructured interviews with 30 participants (24 with direct experienced and 6 with indirect experienced) to reach data saturation. Participants' responses were recorded and transcripted word by word on paper. Data analysis was done with the constant comparison analysis. Rigorance of data was confirmed by participants and also external check. Results: Three main categories were shown as reasons for unwanted pregnancies: feeling of shame due to mental abnormalities related to pregnancy, being alone and lack of social support and fear of unwanted effects of pregnancy. In all, 12 subcategories were found. Conclusion: According to women's experience, feeling of unwanted pregnancy had a psychological reasons. Considering unintended pregnancy as a high risk pregnancy and establishing educational programs for this problem is seemed to be necessary to decrease negative outcomes of unwanted pregnancy. Paper Type: qualitative study.